2022
DOI: 10.1177/15589447211073833
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity of PROMIS With DASH and DVPRS in Transhumeral Amputees

Abstract: Background: We sought to assess whether select domains of the Patient-Reported Outcomes Measurement Information System (PROMIS) significantly correlate with the Disabilities of the Arm, Shoulder, and Hand (DASH) score and the Defense and Veterans Pain Rating Scale (DVPRS) among transhumeral amputees. Methods: We prospectively administered DASH, DVPRS, and PROMIS (including Upper Extremity, Pain Interference, and Pain Behavior domains) testing to patients presenting for consideration of osseointegration after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…The small homogenous sample size, while sufficiently powered to determine concurrent validity, limits the generalizability of findings. This study’s sample size is comparable to other investigations examining PROMIS measure performance (Sabharwal et al, 2022). The lack of concurrent validity between PROMIS Sleep Disturbance and Multidimensional Fatigue Inventory scores reflects other investigators’ research showing sleepiness and fatigue are distinct symptoms that require specific assessment measures be used when assessing symptom severity (Dietch et al, 2016).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The small homogenous sample size, while sufficiently powered to determine concurrent validity, limits the generalizability of findings. This study’s sample size is comparable to other investigations examining PROMIS measure performance (Sabharwal et al, 2022). The lack of concurrent validity between PROMIS Sleep Disturbance and Multidimensional Fatigue Inventory scores reflects other investigators’ research showing sleepiness and fatigue are distinct symptoms that require specific assessment measures be used when assessing symptom severity (Dietch et al, 2016).…”
Section: Discussionsupporting
confidence: 65%
“…The small homogenous sample size, while sufficiently powered to determine concurrent validity, limits the generalizability of findings. This study's sample size is comparable to other investigations examining PROMIS measure performance (Sabharwal et al, 2022). The lack of concurrent validity In this study, the brief six-item short-form PROMIS Fatigue measure demonstrated concurrent validity to the longer and more time-intensive Multidimensional Fatigue Inventory.…”
Section: Discussionsupporting
confidence: 61%
“…The DASH score is a generic questionnaire used for musculoskeletal disorders of the upper limb. While it is not specific for amputations, the questionnaire is widely used internationally, available in many different languages, and was already previously used in amputee populations (28)(29)(30)(31), which enables comparison. Other studies with major unilateral upper limb amputees reported a mean DASH score ranging from 32.8 (30) to 39 (29).…”
Section: Discussionmentioning
confidence: 99%
“…The DVPRS can be of value to clinician scientists conducting pain-related research over longer tools commonly used in research, such as PROMIS, specifically in high volume orthopedic settings. Despite the sample size, which is larger than other investigations of the validity of DVPRS and PROMIS,3 and cross-sectional design, this analysis was able to be conducted with a diverse sample from a medically underserved urban area presenting with injuries commonly seen in orthopedic settings. Future research, recruiting equal numbers of participants across racial and ethnic categories is needed to better ascertain potential differences in acute pain-related measures following orthopedic trauma.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis examined the association between the DVPRS, Pain Numeric Rating Scale (NRS), and Patient-Reported Outcome Measures Information System (PROMIS) in a civilian orthopedic sample. To date, the DVPRS has been validated and predominantly used in military and veteran settings, often with small homogeneous samples 1–3. This analysis offers a larger, diverse civilian sample, presenting with a broad array of injury types, which enhances the generalizability of this work to other high volume orthopedic clinics.…”
Section: Introductionmentioning
confidence: 99%